2015
DOI: 10.1097/tp.0000000000000464
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Urea Excretion and Long-term Outcome After Renal Transplantation

Abstract: Urinary urea excretion, a marker for protein intake, was inversely related to graft failure in RTR with BMI less than 25 kg/m and in RTR with an eGFR of 45 mL per min per 1.73 m or higher. In addition, urinary urea excretion was inversely related to mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
5
19
0
1
Order By: Relevance
“…We conclude that the beneficial effect of USE on reducing the risk of premature graft failure is mainly dependent upon sulfur intake through dietary protein. Our current findings corroborate an earlier study of us where we found that low protein intake, as reflected by low 24 h urinary urea excretion, is associated with increased risk for premature graft failure in RTR [35,36]. The current guideline of the "Kidney Disease: Improving Global Outcomes" workgroup does not provide specific recommendations regarding protein intake for RTR [38], neither does the guideline of the "National Kidney Foundation Kidney Disease Outcomes Quality Initiative" (NKF KDOQI) [39,40].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We conclude that the beneficial effect of USE on reducing the risk of premature graft failure is mainly dependent upon sulfur intake through dietary protein. Our current findings corroborate an earlier study of us where we found that low protein intake, as reflected by low 24 h urinary urea excretion, is associated with increased risk for premature graft failure in RTR [35,36]. The current guideline of the "Kidney Disease: Improving Global Outcomes" workgroup does not provide specific recommendations regarding protein intake for RTR [38], neither does the guideline of the "National Kidney Foundation Kidney Disease Outcomes Quality Initiative" (NKF KDOQI) [39,40].…”
Section: Discussionsupporting
confidence: 93%
“…Dietary sources of sulfate are sulfur-containing amino acids via animal or plant protein or sulfate-rich foods(components), such as beer and preservatives. We found that USE has a very high correlation with urinary urea excretion, which reflects total protein intake in stable RTR [24,35,36]. Additionally, USE is also strongly correlated to estimated total protein intake which can be calculated with the urea nitrogen excretion-derived Maroni formula (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Our study is unique because of the large study population and the ability to study potential mechanisms of the association between protein intake and mortality and graft failure. Recently, we have found in a cohort of 940 RTR that protein intake is inversely associated with mortality and graft failure, similar to this study . We were, however, not able to explain the underlying mechanisms of the association.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, despite significant hypertrophy and hyperfiltration in the remaining kidney after nephrectomy, kidney function remains normal over a prolonged period (>20 y) ( 67 , 68 ). A recent trial found that after kidney transplant there was a negative correlation between protein intake and mortality and graft failure in normal-weight individuals with an eGFR >45 mL ⋅ min −1 ⋅ 1.73 m − 2 ( 69 ), suggesting a protective effect of protein intake on kidney health. Moreover, despite numerous studies that found that an HP diet increases GFR ( 30 , 33 , 49 , 53 , 70 , 71 ), to date there is no evidence linking HP intake to kidney disease in healthy individuals or those at risk of kidney disease due to pre-existing conditions such as obesity, hypertension, or dyslipidemia ( 62 ).…”
Section: Discussionmentioning
confidence: 99%